Bis(mu-2-{1- 2-(dimethylamino)ethylimino ethyl}phenolato)bis bromidocopp er(II) monohydrate - Gwaram, N.S.; Ali, Hapipah Mohd; Khaledi, H. (International Union of Crystallography, 2011)
In the centrosymmetric dinuclear copper(II) title complex, [Cu2Br2(C12H17N2O)(2)]center dot H2O, each Cu-II ion is five coordinated in a square-pyramidal geometry by the N,N',O-tridentate Schiff base, one Br atom and the bridging O atom of the centrosymmetrically related Schiff base. In the crystal, the water molecules link the complex molecules into infinite chains along the b axis via O-H center dot center dot center dot Br and C-H center dot center dot center dot O hydrogen bonds.